2010
DOI: 10.1111/j.1365-2109.2009.02423.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on the growth and proximate composition of selected tropical marine periphytic diatoms and cyanobacteria

Abstract: Marine periphytic cyanobacteria and diatoms have been examined as a potential source of feed supplement for rearing aquatic larvae in the aquaculture industry. Culture of the periphytic diatom Amphora sp., Navicula sp., Cymbella sp. and the cyanobacteria Oscillatoria sp. at di¡erent salinities showed signi¢cant changes in biomass and speci¢c growth rates. Diatoms growth was signi¢cantly higher at 35 g L À 1 , while for cyanobacteria growth was better at 25 g L À 1 . Signi¢cantly higher levels of protein and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 27 publications
2
14
0
1
Order By: Relevance
“…Our results of growth rates were higher than those of marine diatoms Amphora sp., Navicula sp. and Cymbella sp., which showed respective values of 0.45, 0.35 and 0.5 day −1 after 12 days of outdoor culture at 35 ppm salinity (Khatoon, Banerjee, Md Yusoff, & Shariff, ). Our results were also higher than those of Chaetoceros muelleri (0.33 day −1 ) and C. calcitrans day −1 (0.32 day −1 ) when cultivated outdoor using f/2 culture medium and 35 ppm salinity (Velasco, Carrera, and Barros ().…”
Section: Resultssupporting
confidence: 44%
“…Our results of growth rates were higher than those of marine diatoms Amphora sp., Navicula sp. and Cymbella sp., which showed respective values of 0.45, 0.35 and 0.5 day −1 after 12 days of outdoor culture at 35 ppm salinity (Khatoon, Banerjee, Md Yusoff, & Shariff, ). Our results were also higher than those of Chaetoceros muelleri (0.33 day −1 ) and C. calcitrans day −1 (0.32 day −1 ) when cultivated outdoor using f/2 culture medium and 35 ppm salinity (Velasco, Carrera, and Barros ().…”
Section: Resultssupporting
confidence: 44%
“…Oshe et al (2008) cultivated the same species at a salinity of 30 and observed a decrease in growth rate, requiring around seven days to reach the stationary phase. Khatoon et al (2010), in analyzing the effect of salinity on three diatom species (Navicula, Cymbella and Amphora) grown in Conway medium at 28ºC and light intensity of 31.9 μmol.photons m -2 .s -1 , 12:12 h light-dark cycle, obtained a biomass increase from the eighth day of culture, reaching a maximum on the twelfth day at all salinities tested (15, 20, 25, 30 and 35). The same authors found that biomass increased with salinity, in accordance with Ghezelbash et al (2008), who showed that microalgae cultivated at a salinity of 40 g.L -1 had the highest biomass.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of salinity on the production of the potent algal neurotoxin domoic acid has been demonstrated in laboratory experiments (Doucette et al ., ) and is correlated with environmental gradients (Thessen and Stoecker, ; Downes‐Tettmar et al ., ). Depending on the diatom species studied and the laboratory conditions, the cell lipid content and composition have also been found to be modified upon changes in salinity level, with an increase in lipid production at reduced (Wraige et al ., ; Khatoon et al ., ; Garcia et al ., ) or elevated salinity (Rowland et al ., ; Cheng et al ., ) levels. Correspondingly, the expression of several genes involved in lipid biosynthesis, such as the acyl‐CoA synthetase (ACSL), which play a key role in lipid biosynthesis (Cheng et al ., ), has been shown to be significantly upregulated under salinity stress (Maheswari et al ., ; Petrou and Ralph, ).…”
Section: Introductionmentioning
confidence: 98%